Screening of efficient phosphate solubilizing fungi from mine soil and effect of phosphofungi on seed germination and vigour index of ground nut (arachis hypogaea L.) and green gram (vigna radiata L.) - Lokesh, Shanubhoganahalli Thimmappa; Naveen Kumar, Kudure Jayanna; Thippeswamy, Basaiah (International Journal of Biological Research, 2016)
Background: The use of chemical fertilizers to solve the problem of nutrient deficiency in soil has been associated with a number of environmental problems.Objective: The aim of this study was to perform an isolation and screening of native phosphofungi from mine soil. To evaluate the effect of phosphofungi on seed germination and seedling vigour index of Ground nut and Green gram.Materials and Methods: The phosphofungi were screened using Pikovskayaâ€™s agar medium with tricalcium phosphate (Ca3 (PO4)2) as the phosphorus source. The soluble phosphorus, Phosphate solubilizing activity, titrable acidity, pH and fungal biomass were determined. Mineral phosphate solubilizing (MPS) activities of fungal isolates were tested in tricalcium phosphate medium.Results: Five promising phosphate solubilizing fungal species were screened. Aspergillus niger (13Â±1.0 mm) and Aspergillus flavus (8Â±0.6mm) showed the more phosphate solubilising index than compared to other fungal isolates. Analyzing the possible phosphorus released, from 3rd, 6th, 9th, and 12th day of incubation. Antagonistic effect of phosphofungi Aspergillus flavus (65Â±11 mm) and Aspergillus niger (60Â±13 mm) showed more effective against Colletotrichum sp. than compared to other fungal isolates.Â Aspergillus flavus (745Â±20Âµg/ml) and Penicillium spinulosum (600Â±20 Âµg/ml) showed maximum phosphate solubilizing activity on 3rd and 12th day of incubation. Fusarium redolens showed the more effectiveness on seed germination and seedling vigour than compared to other fungal isolates. Aspergillus flavus showed positive result for the production of Indole 3 acetic acid and remain four fungal strains are negative result.Conclusion: Biofertilizers from native phosphofungi could be used alongside reduced levels of inorganic fertilizers to enhance soil available Phosphorous.